The language of online sports commentary in a comparative perspective - Lewandowski, Marcin (Lingua Posnaniensis, 2012)
This paper attempts to describe a relatively new media genre (or as the author prefers to see it, an electronic register), i.e., online sports commentary (OSC). The analysis concerns English-language online live soccer match reports, and is based on a methodological framework proposed by D. Biber and S. Conrad (2009), who in register studies emphasize the correlation between the situational characteristics and lexico-grammatical features of a particular language variety. The paper also aims to compare the register in question with other related varieties, i.e., written sports commentary (WSC) and sports announcer talk (SAT ) in order to corroborate the hypothesis that the register of online commentary is a hybrid of spoken and written language.